KAPABILITAS DINAS KEBUDAYAAN DAN PARIWISATA DALAM PENGEMBANGAN OBJEK WISATA DANAU BUATAN DI KOTA PEKANBARU TAHUN 2022 - Novriana, Rosti; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research is based on the existence of problems related to the development of Artificial Lake attractions which include the condition of inadequate facilities or infrastructure, lack of promotion and a drastic decrease in the number of visitors. This research aims to find out the capabilities of the Culture and Tourism Department of Pekanbaru City in developing Artificial Lake tourist attraction by using the Core Capabilites theory proposed by Leonard and Barton (1992), where data collection techniques include interview and documentation techniques. Then, the data analysis technique used is a qualitative descriptive analysis technique which includes data collection, data reduction, data presentation and conclusion drawing The results of this study indicate that the capabilities of the Culture and Tourism Office of Pekanbaru City do not fully have the ability to develop Artificial Lake tourism objects which can be seen in 4 (four) dimensions of capability, namely knowledge and skills, technical systems, managerial systems and values and norms. First, in the knowledge and skills dimension, the Culture and Tourism Office already has two programs, namely the development of knowledge and skills and the Apparatus Resources capacity building program. Although it has been running, but in the process the two programs are not specific to the development of Artificial Lake tourist attraction and only general knowledge related to culture and tourism. Second, in the technical systems dimension, the Culture and Tourism Office does not yet have standard operational procedures (SOP) and an adequate information system in the development of Lake Buatan tourist attraction. Third, in the managerial systems dimension, the Culture and Tourism Office has collaborated with PT. Sarana Pembangunan Pekanbaru (SPP), but the program planning that has been budgeted is still not implemented and there is still no further coordination for the development of Lake Buatan tourist attraction. Fourth, in the dimension of values and norms, the Office of Culture and Tourism still does not have a Motto, Vision and Mission which indicates a lack of seriousness and commitment of the government in the development of Artificial Lake tourist attraction. Keywords: Capabilities, Development, Tourist Attraction